Between Ethical Oversight and State Neutrality Introducing Controversial Technologies into the Public Healthcare Systems of Germany, Italy and England - Domenici, Irene (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2023)
Introducing ethically controversial (bio)technologies into the public healthcare system inevitably provokes societal and legal conflict. While it is often argued that these choices ought to comply with moral standards, the consideration of ethical and religious concerns raises a serious problem of legitimacy. By adopting the position that the state must act in an ethically neutral manner this book provides a critical legal analysis of the relationship between ethics and law and its implications for the public healthcare system. The ensuing examination combines a comparative, legal-constitutional perspective with the investigation of two case studies: preimplantation genetic diagnosis (PGD) and non-invasive prenatal testing (NIPT).